2001
DOI: 10.1046/j.1365-3083.2001.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Independent Genetic Control of B‐ and T‐Cell Tolerance in Strains of Mouse Selected for Extreme Phenotypes of Oral Tolerance

Abstract: Two strains of mice were genetically selected for susceptibility (TS-Ab/HetS strain) or resistance (TR-Ab/ HetS strain) to oral tolerance of the humoral response by using ovalbumin (OVA). The progressive interstrain divergence produced by bi-directional selective breeding during 15 generations demonstrated the polygenic nature of oral tolerance. This paper shows the humoral and delayed-type hypersensitivity (DTH) responses, after intragastric administration of OVA and subsequent immunization with that immunoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…3a), as in previous results for delayed-type hypersensitivity reaction and IgE responses. 22,29 This dose-dependent . The mean differences between OVA-gavaged TS and OVAgavaged TR were statistically significant (P < 0Á001) by t-test as were those between OVA-gavaged TS and its respective saline-gavaged control (P < 0Á001), and between OVA-gavaged F 2 and saline-gavaged F 2 (P < 0Á01).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…3a), as in previous results for delayed-type hypersensitivity reaction and IgE responses. 22,29 This dose-dependent . The mean differences between OVA-gavaged TS and OVAgavaged TR were statistically significant (P < 0Á001) by t-test as were those between OVA-gavaged TS and its respective saline-gavaged control (P < 0Á001), and between OVA-gavaged F 2 and saline-gavaged F 2 (P < 0Á01).…”
Section: Discussionmentioning
confidence: 88%
“…Immunoglobulin G antibodies of TR and TS mice to OVA and other antigens such as casein (Sigma-Aldrich), fowl gamma globulin (IgY), peanuts and cashew nuts were assessed by enzyme-linked immunosorbent assay (ELISA) as described previously. 22 Tetramethylbenzidine (Zymed Lab., Inc., San Francisco, CA) was used as the substrate for horseradish peroxidase. The yellow colour produced was read at 450-nm wavelength using a multiscan photometer.…”
Section: Evaluation Of Humoral Responsementioning
confidence: 99%
“…Furthermore, it has to be kept in mind that even between different mice strains significant differences in the induction of oral tolerance were observed (da Silva et al, 1998(da Silva et al, , 2001, highlighting the importance of basic research in another species like humans.…”
Section: Oral Tolerance In Human Autoimmune Diseasesmentioning
confidence: 99%
“…The investigation of genes controlling acquired or innate immune mechanisms has demonstrated that major immunobiological functions such as inflammatory responses, quantitative antibody production, immunological tolerance, and T cell-mediated reactivity, in spite of their functional integration are, at least in part, under the additive effect of independent segregating loci (22)(23)(24)(25). The resulting polymorphic regulation of innate and adaptive immunity is the fundamental characteristic ensuring the survival of a genetically heterogeneous natural population.…”
Section: Introductionmentioning
confidence: 99%